Os ritmos, a vida cotidiana e a produção do espaço no povoado de Placa Santo Antônio em Juscimeira-MT - Silva, Juliana Rodrigues da (2021)
The present work sought to understand the changes in daily life and in the production of space in Placa Santo Antonio, by means of ritmanalysis in the context of the global-local relationship induced by the capitalist mode of production. Placa Santo Antônio, which belongs to the municipality of JuscimeiraMT, is a small village that began its formation process in the 1960s. In the beginning, its occupation process was focused on the farms around the village, and as other residents arrived, they formed the urban part of the village, which in the 1970s was practically formed. Throughout its history, this community has undergone transformations, mainly those linked to the mode of production, and in order to understand these changes, the dialectic logic served as an interpretative basis for this investigation, allowing the apprehension of knowledge that is closer to the reality experienced by the residents of the village. The field work along with the interviews served to get to know the social and economic profile of the village, in addition to providing information about the historical process of formation of the community. In this way it was possible to observe that this community had, as its foundation, agricultural activities focused on simple mercantile production, and later on the introduction of cattle farming. This type of production lost space not only for the areas destined for pasture, but also for the sugarcane plantations that sprang up around the village as a result of the expansion of the cultivation areas destined to supply the Jaciara Mill. Thus, it can be concluded that the changes in the daily life of this community were directly linked to the capitalist mode of production, which seeks large-scale production for profit.